2016
DOI: 10.1136/emermed-2015-205365
|View full text |Cite
|
Sign up to set email alerts
|

The effect of provision of pain management advice on patient satisfaction with their pain management: a pilot, randomised, controlled trial (pain advice trial)

Abstract: Objective We aimed to provide pain advice ('The treatment of pain is very important and be sure to tell the staff when you have pain') as an intervention and evaluate its effect upon patient satisfaction. The purpose of this pilot trial was to ensure the design and methods of a future trial are sound, practicable and feasible. Method We undertook a pilot, randomised, controlled, clinical intervention trial in a single ED. The control arm received standard care. The intervention arm received standard care plus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…The secondary outcome was patient satisfaction with their pain management, specifically the proportion of patients who were ‘very satisfied’ 18. This level of satisfaction was chosen as the primary outcome as it is a patient-centred target for the ED staff.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The secondary outcome was patient satisfaction with their pain management, specifically the proportion of patients who were ‘very satisfied’ 18. This level of satisfaction was chosen as the primary outcome as it is a patient-centred target for the ED staff.…”
Section: Methodsmentioning
confidence: 99%
“…Approximately 48% of patients treated in our ED are ‘very satisfied’ with their pain management 18. We hypothesised that more patients who receive analgesia would be ‘very satisfied’ than patients who do not and that a clinically significant difference in the proportions who are ‘very satisfied’ is 15%, for example, 50% vs 35%, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies from Australia have shown that providing adequate analgesia improves patient satisfaction . A very simple intervention that may improve patient satisfaction is to say to patients that ‘the treatment of pain is very important and be sure to tell the staff that you have pain’ . More complex educational initiatives may also result in improved quality of pain care as has previously been demonstrated in Australia with the National Pain Management Initiative .…”
Section: Discussionmentioning
confidence: 99%
“…A ‘cold call’ has been defined as a telephone call soliciting business made directly to a potential customer without prior contact or without a lead . While this definition is drawn from the commercial setting, the cold calling technique is used in emergency medicine research, especially for the collection of outcome data at patient follow up . In general, cold calling is regarded as a less than optimal research practice and our recent experience exemplifies the reasons for this.…”
mentioning
confidence: 99%